A Numerical Method for Solving a Class of Continuous-Time Linear Fractional Programming Problems - Ching-Feng Wen; Yung-Yih Lur; Sy-Ming Guu (2009 International Joint Conference on Computational Sciences and Optimization : 24-26 April 2009, 2009)
In this paper, we discuss a class of infinite-dimensional optimization problems called continuous-time linear fractional programming problems (FP). We provide a discrete approximation procedure to find numerical solutions of (FP) and to establish the estimation for the error bound of approximate solutions. Moreover, in order to reduce the consumption of computational time of solving large scale finite-dimensional linear programs, we further develop recurrence algorithms to take over the conventional methods.